Paracrine Effects of Mesenchymal Stem Cells Induce Senescence and Differentiation of Glioblastoma Stem-Like Cells. Issue 4 (April 2015) - Kološa, Katja; Motaln, Helena; Herold-Mende, Christel; Koršič, Marjan; Lah, Tamara T.
Glioblastoma multiforme (GBM) displays high resistance to radiation and chemotherapy, due to the presence of a fraction of GBM stem-like cells (GSLCs), which are thus representing the target for GBM elimination. Since mesenchymal stem cells (MSCs) display high tumor tropism, we examined possible antitumor effects of the secreted factors from human MSCs on four GSLC lines (NCH421k, NCH644, NIB26, and NIB50). We found that conditioned media from bone marrow and umbilical cord-derived MSCs (MSC-CM) mediated cell cycle arrest of GSLCs by downregulating cyclin D1. PCR arrays revealed significantly deregulated expression of 13 genes associated with senescence in NCH421k cells exposed to MSC-CM. Among these, ATM, CD44, COL1A1, MORC3, NOX4, CDKN1A, IGFBP5, and SERPINE1 genes were upregulated, whereas IGFBP3, CDKN2A, CITED2, FN1, and PRKCD genes were found to be downregulated. Pathway analyses in GO and KEGG revealed their association with p53 signaling, which can trigger senescence via cell cycle inhibitors p21 or p16. For both, upregulated expression was proven in all four GSLC lines exhibiting senescence after MSC-CM exposure. Moreover, MSC paracrine signals were shown to increase the sensitivity of NCH421k and NCH644 cells toward temozolomide, possibly by altering them toward more differentiated cell types, as evidenced by vimentin and GFAP upregulation, and Sox-2 and Notch-1 downregulation. Our findings support the notion that MSCs posses an intrinsic ability to inhibit cell cycle and induce senescence and differentiation of GSLCs.